PENERAPAN METODE MUROJA’AH JADID DAN QODIM DALAM MENJAGA KUALITAS HAFALAN AL-QUR’AN - NURUL INSANNI; Nur Hidayah; Muin Abdullah (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
Abstract : The purpose of this research is to find out 1) How is the application of the muraja'ah Jadid and qodim methods in maintaining the quality of memorizing the Qur'an in SDIT Taruna Al-Qur'an Yogyakarta students, 2) Supporting and inhibiting factors in maintaining the quality of memorizing the Al-Qur'an 'an student at SDIT Taruna Al-Qur'an Yogyakarta. The aim of this research is discovering the property of the implementation murajaah jadid and qodim technique in memorizing Qur'an. The data is taken from observation, interviewing and documentation. While the data analysis was done by data collection, reducing data, data presentation and withdrawing the conclusion. Before the researcher applied the murajaah jadid and qodim, the researcher finds out that almost the students in SDIT Taruna Al-Qur’an Yogyakarta lack of motivation, passion and parents' support. It gives a big impact on their quality of memorization Qur'an. After the researcher applying the murajaah qodim and murajaah jadid in SDIT Taruna Al-Qur’an Yogyakarta, the researcher and the teacher find out that it made the students quality of memorazation Qur'an is increasing. The conclusion of this research shows that this research is successful.